Formulasi dan Karakterisasi Self Nano-Emulsifyin Drug Delivery System (SNEDDS) Simvastatin dengan PEG 400 sebagai Kosurfaktan - Patmayuni, Dewi; Rosalia, Nadia; Rikmasari, Yopi; Sri Wahyuni, Yenni (Jurnal Kesehatan Saelmakers PERDANA (JKSP), 2024)
Solubility is a problem in a drug characteristic, because drugs with low solubility will cause low bioavailability and effectiveness. Simvastatin is one of the drugs for hypercholesterolemia that has low solubility, so it needs modification to increase its solubility. Self Nano-Emulsifying Drug Delivery System (SNEDDS) is one of the modifications of drug delivery system that can increase the solubility. SNEDDS is formulated with VCO as oil, tween 80 as surfactant and PEG 400 as cosurfactant. The purpose of this study is to obtain the formula with the best characteristics of the PEG 400 variations of 1g, 2g and 3g. SNEDDS preparations were carried out organoleptic tests, phase separation tests, % transmittance tests, pH tests, viscosity tests, emulsification time tests and characterization include of droplet size, polydispersity index and zeta potential was measured by Particle Size Analyzer (PSA). Based on the tests that have been carried out, the best formula of SNEDDS simvastatin was obtained at a concentration of PEG 400 1g, with the characteristics in order, namely in the form of a slightly thick liquid with a transparent yellow color and a distinctive smell of VCO, no phase separation was formed either in the centrifugation method or during storage of 28 days, the transmittance % was 97.966%, pH 8.886, viscosity was 28.206, and the emulsification time was 57.176. The results of characterization using PSA instruments were 16.323 nm, 0.266 and -13.61 mV, respectively. The lower the concentration of PEG 400 the better the characteristics of the preparation.